Houston--a modern city. - Hopkins & Motter (1912)
Available also through the Library of Congress Web site as a raster image.; LC Panoramic maps (2nd ed.), 916; Perspective map not drawn to scale.; AACR2: 651/1; Bird's-eye-view.; Includes illus. and text.